Philosophy of mind - "Beakley, Brian (ed.)" (London, 2006)
The Philosophy of Mind remains the only sourcebook of primary readings offering in-depth coverage of both historical works and contemporary controversies in philosophy of mind. This second edition provides expanded treatment of classical as well as current topics, with many additional readings and a new section on mental content. The writers included range from Aristotle, Descartes, and William James to such leading contemporary thinkers as Noam Chomsky, Paul and Patricia Churchland, and Jaegwon Kim. The 83 selections provide a thorough survey of five areas of enduring controversy: the mind-body problem, mental causation, mental content, innatism and modularity, and associationism and connectionism. Each section includes an introductory overview of the topic by the editors as well as suggestions for further reading. The selections added for the second edition serve both to enhance historical coverage and to update contemporary issues, especially in areas of current empirical research such as connectionism and innatism. Changes to historical coverage include a wider array of readings on classic positions as well as neglected precursors to views often considered recent innovations. The section on the mind-body problem in particular has been greatly expanded, including numerous selections on consciousness and phenomenal qualities (qualia). The book is ideal for both undergraduate and graduate courses in philosophy and the history of psychology and will be useful both as a reference for researchers and a self-contained survey for the general reader.
Keywords: Philosophy of mind